2006
DOI: 10.1615/critrevbiomedeng.v34.i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Microdamage in Bone: Implications for Fracture, Repair, Remodeling, and Adaptation

Abstract: Fatigue microdamage accumulates in bone as a result of physiological loading. The damage is often manifested as microcracks, which are typically 50-100 mum long. These types of cracks develop in the interstitial bone and frequently abut osteon cement lines. In vitro experimentation has shown that an accumulation of fatigue damage reduces the material properties of bone (e.g., elastic modulus). An accumulation of fatigue damage has been implicated in the etiology of stress fractures and fragility fractures. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 0 publications
1
47
1
Order By: Relevance
“…8,47 Several factors may explain, in part, the disagreement between Wenzel et al and the current study, including the age range of subjects (greater in Wenzel et al than in current study), and the vertebral body examined (T12 vs. L2), and the location of the trabecular core within the vertebral body. 6 Regarding our finding that microdamage was not associated with trabecular bone mechanical properties, Fazzalari et al 8 also found no relationship between the amount of microdamage and the ultimate failure stress in trabecular bone specimens from human femurs.…”
Section: Discussioncontrasting
confidence: 75%
“…8,47 Several factors may explain, in part, the disagreement between Wenzel et al and the current study, including the age range of subjects (greater in Wenzel et al than in current study), and the vertebral body examined (T12 vs. L2), and the location of the trabecular core within the vertebral body. 6 Regarding our finding that microdamage was not associated with trabecular bone mechanical properties, Fazzalari et al 8 also found no relationship between the amount of microdamage and the ultimate failure stress in trabecular bone specimens from human femurs.…”
Section: Discussioncontrasting
confidence: 75%
“…This has been demonstrated several times by different laboratories using different animal models and is now considered an integral component of bone remodeling physiology [20][21][22][23][24] (Fig. 4).…”
Section: Introductionmentioning
confidence: 84%
“…But why do the osteocytes die with fatigue loading? The most prominent hypothesis is that osteocyte processes are physically broken by microdamage, disrupting cell-to-cell communication and fluid flow [20,23]. This is supported by the abundance of evidence showing fluid flow plays a key role in osteocyte physiology [21,46,47] and that both fluid flow [35,48] and cell process connections [49] are disrupted following fatigue loading.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we use the term "bone quality" as the quality of the bone matrix thus comprising mineralization, posttranslational changes in the collagen molecule that occur with age, and microscopic tissue damage which all are parameters affected by bone remodeling. Recent developments in the field of biochemical marker research have indicated that age-related changes in bone matrix molecules are associated with bone fracture resistance independent of BMD and may thus allow for the monitoring of some aspects of bone matrix quality in a manner that is noninvasive [17,18,[22][23][24][25][26][27][28][29]. In this review, we emphasize the likely connection between bone matrix quality and bone remodeling, highlighting the importance of bone matrix age.…”
Section: Introductionmentioning
confidence: 98%